Urinary epidermal growth factor, monocyte chemoattractant protein-1 or their ratio as predictors for rapid loss of renal function in type 2 diabetic patients with diabetic kidney disease - Bancha Satirapoj (2019)
© 2018 The Author(s). Background: Increased monocyte chemoattractant protein-1 (MCP-1) and decreased epidermal growth factor (EGF) are promising biomarkers to predict progressive decline in kidney function in non-diabetic kidney diseases. We aimed to evaluate the performance of urinary EGF, MCP-1 or their ratio in predicting rapid decline of GFR in a cohort of Type 2 diabetic patients (T2DM) with diabetic kidney disease (DKD). Methods: T2DM patients (n = 83) with DKD at high risk for renal progression were followed up prospectively. The baseline urine values of MCP-1 to creatinine ratio (UMCP-1), EGF to creatinine ratio (UEGF), EGF to MCP-1 ratio (UEGF/MCP-1) and albumin to creatinine ratio (UACR) were measured. The primary outcome was a decline in estimated glomerular filtration rate (GFR) of ≥25% yearly from baseline. Results: During follow-up time of 23 months, patients with rapid decline in estimated GFR of ≥25% yearly from baseline had significantly higher baseline levels of UMCP-1, and UACR and lower UEGF and UEGF/MCP-1 ratio. All renal biomarkers predicted primary outcomes with ROC (95%CI) for UMCP-1=0.73 (0.62-0.84), UEGF=0.68 (0.57-0.80), UEGF/MCP-1=0.74 (0.63-0.85), and UACR =0.84 (0.75-0.93). By univariate analysis, blood pressure, GFR, UACR, UMCP-1, UEGF, and UEGF/MCP-1 were associated with rapid decline GFR. By multivariate analysis, UACR, systolic blood pressure, and UMCP-1 or UEGF/MCP-1 were independently associated with rapid GFR decline. Conclusions: UMCP-1 or UEGF/MCP-1 ratio were associated with rapid renal progression independent from conventional risk factors in DKD.